Synthesis and Characterization of Hydroxyapatite- (HAP-) Clay Composites and Adsorption Studies on Methylene Blue for Water Treatment - Ebenezer Annan; Grace Karikari Arkorful; David Sasu Konadu; Bernard Asimeng; David Dodoo-Arhin; Martin Egblewogbe (Journal of Chemistry)
Dyes used by the textile, tannery, and food industries tend to pollute water bodies and must be removed to get clean water. Hydroxyapatite (HAP) was synthesized from eggshells using the wet precipitation process. The as-synthesized HAP was characterized using Fourier Transform Infrared (FTIR) and X-ray powder diffraction (XRD). The synthesized HAP was mixed with three different clays: halloysite (HNT), kaolinite (KAO), and bentonite (BENT). The removal efficiency values of methylene blue (MB) from the data showed that HAP-BENT adsorbents had higher values, followed by HAP-HNT and then HAP-KAO adsorbents. The combined masses of 24 mg, 34.5 mg, and 33 mg (representing 20%, 15%, and 10% of HAP-BENT mass) had average adsorption capacity values of 20.7 mg/g, 17.2 mg/g, and 17.9 mg/g, respectively. For each mass percentage, the adsorption capacity values were found to decrease with adsorbent dosage. The HAP-BENT composites had removal efficiency values of 98.4, 91.9%, and 91.9%, respectively. Adsorption data for the HAP-BENT adsorbents were found to be well described by the Langmuir isotherm model and pseudo-second-order kinetic model. The effect of temperature on adsorption capacity was evaluated and thermodynamical modeling was undertaken. The thermodynamical modeling predicts that based on the value of the change in enthalpy and Gibbs free energy the process was exothermic and spontaneous. This work confirms the potential of HAP-clay composites in removing MB from water.